Analisis Kadar Siklamat pada Es Krim di Kota Banjarbaru - Nurlailah Nurlailah; Nurhayati Aslami Alma; Neni Oktiyani (Medical Laboratory Technology Journal, 2017)
Sweeteners are one of the components which are often added to foodstuffs. Synthetic sweeteners are widely circulated in the community is cyclamate. Consumption of cyclamate that exceeds the dose will lead to bladder cancer. It will also cause lung, liver, and lymph tumors. The purpose of this study was to determine the presence of cyclamate in ice cream that exceeded the required threshold. The type of this research is the descriptive survey. The sample of this research is ice cream that produced by household companies from all ice cream traders in North Banjarbaru with 11 ice cream sellers. The variables in this study were cyclamate content found in ice cream. The results showed that 11 samples of ice cream were examined, 9 samples containing cyclamate with the highest level of 7.37 g / kg as cyclamic acid. The conclusion of this study is ice cream containing cyclamate found as much as 82% (9 samples), while 18% (2 samples) others negative, from 9 samples containing cyclamate positive, 89% did not qualify the requirements of PERMENKES Number 208 in 1985 that exceeds 2 gr/Kg as cyclamate acid. More specific checks are required for the analysis of cyclamate levels by other methods such as High Performance Liquid Chromatography.